Etnik Identitas dalam Sengketa Wilayah: Telaah Kritis Konflik Kepemilikan Empat Pulau Aceh-Sumatera Utara dalam Perspektif Kebijakan Administrasi Publik - Kartius, Kartius; Yusran, Rahmadani (Asosiasi Ilmuwan Administrasi Negara (AsIAN), 2025)
The territorial dispute between the provinces of Aceh and North Sumatra over four islands in the Aceh Singkil coastal area is not merely an administrative matter, but also reflects tensions rooted in collective political identity. This study aims to analyze the dynamics of the conflict by employing a theoretical framework of political identity, territorial identity, and symbolic-cultural approaches (Anderson, 1991; Donnan & Wilson, 2021). The research adopts a qualitative-descriptive method with a single case study design, using document analysis, digital media sources, and recent academic literature. The findings indicate that the Acehnese community perceives the four islands as integral to their historical memory, cultural heritage, and collective symbolism of the “Tanah Rencong.” In contrast, the central government's technocratic approach, which neglects symbolic and collective memory dimensions, has triggered widespread social resistance. This article underscores the importance of spatial policies that are contextual, deliberative, and sensitive to identity plurality. The study contributes to the development of identity-based public policy analysis and supports conflict resolution strategies that acknowledge the symbolic dimension of territorial governance.